Specialist nurse intervention to reduce unscheduled asthma care in a deprived multiethnic area: the east London randomised controlled trial for high risk asthma (ELECTRA). Issue 7432 (12th January 2004) - Griffiths, Chris; Foster, Gill; Barnes, Neil; Eldridge, Sandra; Tate, Helen; Begum, Shamoly; Wiggins, Mo; Dawson, Carolyn; Livingstone, Anna Eleri; Chambers, Mike; Coats, Tim; Harris, Roger; et al.
Abstract : Objective To determine whether asthma specialist nurses, using a liaison model of care, reduce unscheduled care in a deprived multiethnic area. Design Cluster randomised controlled trial. Setting 44 general practices in two boroughs in east London. Participants 324 people aged 4-60 years admitted to or attending hospital or the general practitioner out of hours service with acute asthma; 164 (50%) were South Asian patients, 108 (34%) were white patients, and 52 (16%) were from other, largely African and Afro-Caribbean, ethnicities. Intervention Patient review in a nurse led clinic and liaison with general practitioners and practice nurses comprising educational outreach, promotion of guidelines for high risk asthma, and ongoing clinical support. Control practices received a visit promoting standard asthma guidelines; control patients were checked for inhaler technique. Main outcome measures Percentage of participants receiving unscheduled care for acute asthma over one year and time to first unscheduled attendance. Results Primary outcome data were available for 319 of 324 (98%) participants. Intervention delayed time to first attendance with acute asthma (hazard ratio 0.73, 95% confidence interval 0.54 to 1.00; median 194 days for intervention and 126 days for control) and reduced the percentage of participants attending with acute asthma (58% (101/174) v 68% (99/145); odds ratio 0.62, 0.38 to 1.01). In analyses of prespecified subgroups the difference in effect on ethnic groups was not significant, but results were consistent with greater benefit for white patients than for South Asian patients or those from other ethnic groups. Conclusion Asthma specialist nurses using a liaison model of care reduced unscheduled care for asthma in a deprived multiethnic health district. Ethnic groups may not benefit equally from specialist nurse intervention.